Why Stop? - Awbrey, Betty Dooley (Houston, Texas : Gulf Publishing Co., 1978)
A Guide to Texas Historical Roadside Markers
Keywords: Historical markers -- Guidebooks -- Texas; Legends -- Texas; Texas -- History, Local; Texas -- Guidebooks